Rational therapeutic targeting of myeloid cells in glioblastoma: challenges and perspectives - Faruk Akay; Maya Saleh (Frontiers in Immunology)
Glioblastoma (GB) is the most aggressive tumor of the central nervous system (CNS), accounting for almost 80% of all primary brain tumors. Despite standard-of-care consisting of surgical resection, when possible, adjuvant radiotherapy (RT) and chemotherapy with Temozolomide (TMZ), GB remains highly fatal, with an estimated recurrence rate of over 90% and a median overall survival (OS) of around 15 months from diagnosis. Several factors contribute to such poor patient outcome, including a unique myeloid-rich tumor microenvironment (TME) that confers immunosuppression and therapeutic resistance. Multi-omics, single-cell transcriptomics and multi-modal spatial analyses of GB are unraveling the diversity of brain myeloid cells, including activated microglia, border-associated macrophages (BAM), and monocyte-derived glioma-associated macrophages (GAM), instructed by ontogeny, spatial distribution, cell-cell interactions and response to metabolic cues in the TME. In this review, we elaborate on the heterogeneity and plasticity of myeloid cells in GB and discuss the promise and challenges for rational therapeutic targeting of GAMs in GB.